Entitled Implementation of the Independent Curriculum: Differentiated Learning in Business Chinese Courses - Sheyla Silvia Siregar; Sheyra Silvia Siregar (Universitas Negeri Semarang, 2023)
This research is entitled Implementation of the Independent Curriculum: Differentiated Learning in Business Chinese Courses. The Merdeka Belajar Curriculum is one of the new policies of the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia (Kemendikbud Ristek RI) aimed at realizing an innovative learning process and following the needs of students (student-centered). The purpose of this study is to describe how the application of differentiated learning methods in Business Chinese courses. The method applied to this study is qualitative descriptive with the presentation of non-statistical data. This research will describe the application of differentiated learning in Business Chinese lectures with independent curriculum standards. The focus of the study in this research is the design of the application of differentiated learning methods based on material aspects with the implementation of learning in an independent curriculum with textbooks used in lectures. The study of learning techniques used to draw conclusions through the identification of certain message characteristics and carried out objectively and systematically.